DECOLONIZE THE MEETING WITH DEATH FROM THE AFFECT: interdisciplinary work experience around the exhumation of mass graves in Mexico - Robledo Silvestre, Carolina (Universidade de Brasília, 2019)
In this paper, I propose some reflections on the colonial effects of the forensic turn as a dominant epistemic field to deal with death in contexts of mass crimes and the exhumation of human remains. I consider my own observations done in more than a decade of ethnographic work with relatives of missing persons and three years of ethnography by the mass grave in Mexico. Finally, in an act of political imagination, I propose a project of an emotional science that makes possible to decolonize the exhumation field, from collaborative research processes against the epistemic violence around the treatment of death and justice and the recognition of social, symbolic and spiritual resources that communities have to deal with the excess of atrocities.